Pendidikan Agama Kristen Melalui Musik Kas Teh di Tobelo Halmahera Utara - Angelbest Samalagi; Ellen Kambey; Deflita R.N. Lumi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to examine and decrypt how Christian religious education through music Kas Teh in Tobelo. In terms of Christian education, this music is very good to be preserved and developed in the community and church because the educational value contained in it is very high. This research is qualitative research conducted in Tobelo North Halmahera. The lack of awareness of the community and church in Tobelo towards the Christian values contained in this music is one of the reasons researchers raised the title "Christian Religious Education Through Kas Teh Music in Tobelo, North Halmahera Regency, North Maluku Province". From the results of research conducted by researchers, it is very clear that, people are very unaware of the existence of Christian Values in the music, but Christian Religious Education through Kas Teh music has been carried out when its implementation indirectly leads to Christian values such as loving each other, helping each other, forgiving each other and living in Love.